Measurement of blood flow velocity waveforms in the carotid, brachial and femoral arteries during postural change - Noor Azmi, Azran Azhim; M., Katai; M., Akutagawa; Y., Hirao; K., Yoshizaki; S., Obara; M., Nomura; H., Tanaka; H., Yamaguchi; Y., Kinouchi (IEEE, 2006)
The purpose of this study was to measure blood flow velocities in carotid, brachial and femoral arteries simultaneously during passive postural change using our developed telemetry measurement system. This system was implemented with synchronized measurement of electrocardiogram (ECG). The velocity waveforms and ECG were continuously measured in six putatively healthy young subjects for 130 s during passive postural changes in supine and 90 degrees head-up-tilt (HUT), respectively. Peak systolic SI and end-diastolic d velocities were obtained from the velocity waveforms in 3 arteries, and using these velocities as an index of d/Sl to assess the velocity waveforms during the postural change. The velocity waveforms of 3 arteries, heart rate (HR), and blood pressure (BP) were assessed for 20 s at the stages of postural change. As a result, HTJT-induced increase in HR was more pronounced in the young subjects. The index of d/Sl in carotid was significantly decreased during HUT, whereas the index of that in brachial and femoral arteries were significantly increased. There was significant increase in diastolic BP but, a non significant change in systolic BP to tilt. The decreased of the blood flow index in the carotid artery was expected to be the effect of cerebral autoregulation (CA) to control blood flow to the brain. In contrast, the blood flow in the brachial and femoral was more influenced of venous pressure (VP) in postural change. In conclusion, HUT produced larger changes in the 3 arteries, particularly in brachial and femoral, and also in HR and diastolic BP. This study demonstrated that synchronized measurement of blood flow velocity waveforms in carotid, brachial, and femoral in HUT postural change using our telemetry measurement device was attainable. Thus, this method could prove to be a useful tool for investigating cardiovascular disease (CD) risk with further research and development.